Car sharing schemes and MaaS: A study of shifting mobility practices from ownership to access: Artikel - Christensen , Toke Haunstrup; Friis, Freja; Nielsen, Marie Vang (Proceedings from the Annual Transport Conference at Aalborg University, 2021)
Transport levels and private car use continue to increase worldwide representing complex challenges to climate change mitigation and the liveability of cities. In recent years, interest has arisen in the concept of Mobility-as-a-Service (MaaS) as one possible path towards sustainable mobility futures. MaaS builds on the idea of a shift from private car ownership to a seamless and integrated system providing access to multimodal mobility options including public transport and shared mobility services like car and bike sharing. Currently, only few examples of MaaS schemes exist and knowledge of user experiences is limited. The aim of this paper is to contribute to a better understanding of how shared mobilities, like in MaaS, fit with the everyday life of citizens. Methodologically, the paper draws on insights from qualitative interviews with families using a car sharing scheme in Copenhagen. The interviews are informed by a practice theoretical approach to study the potential of integrating car sharing within the complex of social practices from which the everyday life consist. To inform the discussion of our empirical results, and their implications for future MaaS designs, we base our study on a literature review of existing studies of user experiences with MaaS and an analysis of user practice representations in existing MaaS trials. Our findings indicate three ways forward to promote MaaS as an alternative to private cars. First, future MaaS designs should aim to acknowledge the importance of the interconnections between mobility and other everyday practices. Second, the shift from ownership to access provides several positive benefits like modal flexibility and a new sense of freedom, which the future MaaS design should focus strategically on in order to challenge the ideals around individual ownership. Third, strategic interventions that privilege sustainable mobility solutions through effective initiatives such as road-pricing and physical limitations in private car traffic and parking are needed.